PENGENALAN KEWIRAUSAHAAN MELALUI KEGIATAN MARKET DAY: PEMANFAATAN PRODUK MATCHA SEBAGAI MEDIA PEMBELAJARAN DI PAUD - Siti Rahmawati; Risbon Sianturi; Reny Hayuningrum; Ismi Nuraini; Iyin Rahmawati (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to describe the implementation of Market Day as a learning activity to introduce entrepreneurship to young children through the use of matcha products as an instructional medium. This research employed a literature review method by analyzing journals, books, and curriculum documents related to early childhood entrepreneurship education. The findings indicate that Market Day provides direct learning experiences that help children understand simple buying and selling processes, recognize basic value exchange, and develop social, communication, creative, and fine motor skills. The use of matcha as learning material supports the activity because it is easy to process, visually appealing, and safe, which increases children’s engagement during the learning process. The review also highlights the essential role of teachers as facilitators in ensuring that the learning environment remains structured, secure, and enjoyable. Overall, matcha-based Market Day activities serve as a thematic strategy that is relevant for cultivating entrepreneurial values while integrating multiple developmental domains in early childhood education. The study emphasizes that experience-based learning can be an effective approach to fostering entrepreneurial interest and character from an early age.